Genetic mechanisms and a stability evaluation of large landslides in Zhangjiawan, Qinghai Province - Wu, Yuanzao; Dong, Yangdan; Wei, Zhanxi; Dong, Jianhui; Peng, Liang; Yan, Pan; Ma, Wenli (Frontiers in Earth Science, 2023)
It is important to study the instability law of typical landslides to understand the evolution of regional landslides and for disaster prevention. This study uses the Zhangjiawan landslide in Xining City, Qinghai Province, as an example. Through field surveys and an analysis of the geological environmental conditions, the formation and evolution mechanisms of the Zhangjiawan landslide are summarized. The stability of the Zhangjiawan landslide was evaluated using limit equilibrium and numerical simulation methods to provide theoretical support for the susceptibility of the Zhangjiawan landslide. The results show that the main reasons for the occurrence of multi-grade landslides are the steep and gentle terrain changes, the poor permeability of the mudstone lithology, the excavation of the front anti-slide section, and rainfall. The whole deformation and failure mechanism of the landslide is the “unloading rebound-tension deformation-creep deformation.” The results of the numerical simulation and the limit equilibrium methods are nearly the same, and the difference in the stability coefficients is small. Under rainstorm conditions, the displacement and the maximum shear strain increments are mainly concentrated on the rear edge of the landslide mass, and the front edge is pushed, which is a typical push-type landslide.